Correlation of platelet count and platelet volume indices with coronary artery diseases - Gamit, Mital; Rathod, Gunvanti (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Coronary artery disease is the most common non-communicable disease in the world. Platelet activation plays a central role in the transformation of atherosclerotic cardiovascular disease (CVD) into its potentially major adverse clinical events, such as ischemic stroke and myocardial infarction. Aim and objectives: The aim of this study was to study platelet parameters e.g. platelet count, mean platelet volume, platelet distribution width, and mean platelet concentrate in the spectrum of ischemic artery disease and to attempt a clinicopathological correlation. Materials and methods: This study was done in the hematological section of the pathology department at tertiary care hospital over a period from January 2016 to December 2018. The study population was divided into three groups healthy control, patients of myocardial infarction, and unstable angina. Results: The difference in mean platelet indices between the 3 study groups was significantly higher in MI and UA groups compared to healthy control. Mean platelet count in the control group was 2.60 Lac (± 0.92), cases of MI 2.34 Lac (±0.67), and in cases of unstable angina 2.56 Lac (±0.89). Mean platelet volume in the control group was 8.07 (±2.11), in cases of MI 12.3 (±1.98) and in cases of unstable angina 11.6 (±2.01). Conclusion: From the present study, it can be conclude that larger platelets can play a significant role in CAD. As platelet volume indices (PVI) can provide an alarming sign for the prethrombotic state in IHD. So in day to day routine hematological analysis of PVI and large platelets can help in the management of coronary artery disease.